YOUTH TRANSFORMATION IN KUTAYU VILLAGE THROUGH HADROH CULTURE - Syafik Muhammad; Hidayat Nur Wahid; Hilma Nur Ashlakha; Umi Salamah (Jurnal Intelek Insan Cendikia, 2025)
This research examines the transformation of youth in Kutayu Village through hadroh culture, which contributes to strengthening religious and social values. Utilizing a qualitative approach with a case study method, this study aims to understand how youth involvement in hadroh influences character development, spiritual enhancement, and social bonding within their community. Data were collected through observations, interviews, and documentation, then analyzed descriptively. The findings indicate that hadroh serves not only as a form of religious entertainment but also as a platform for moral and social education among young people. Participation in hadroh fosters discipline, strengthens solidarity, and reinforces Islamic cultural identity among the youth of Kutayu Village. Therefore, efforts to preserve hadroh culture require support from the community and stakeholders to ensure that the positive values embedded in this traditional art form are maintained and passed down to future generations as an integral part of local cultural identity.